Flexibility in faithfulness of Dark-bellied Brent Geese Branta b. bernicla to moulting sites - Ebbinge, Bart S.; Prokosch, Peter; Spaans, Bernard; Müskens, Gerhard J.D.M.; Bom, Roeland; Kokorev, Yakov I.; Syroechkovskiy, Evgeny E. (Wildfowl, 2013)
The distribution of Dark-bellied Brent Geese Branta b. bernicla moulting on the Taimyr Peninsula, in the Russian arctic, varies between years depending on whether the birds had a successful breeding season. Counts made of moulting flocks show that major shifts in numbers occur, particularly in non-breeding years, when in line with Salomonsen’s (1968) hypothesis a higher proportion of the population moults further north. For instance, the delta of the Lower Taimyr River in the northern part of the Taimyr Peninsula held 10-times more moulting Dark-bellied Brent Geese in 1989, a non-breeding year, than it did in the good 1990 breeding season. At a more local scale, in good breeding years family groups with small goslings tend to move away from breeding islands in the Pyasina Delta, western Taimyr, to avoid gosling predation by Taimyr Gulls Larus taimyrensis which nest in colonies on the same islands, whereas in poor breeding years adult geese concentrate on these same islands to moult and avoid the mainland sites used for moulting in good breeding years. Failed breeders have greater freedom than parent birds to choose where to moult as successful breeders remain with their goslings to protect and guide them to the safest nursery and moult areas. Re-captures of ringed Darkbellied Brent Geese at a moulting site in the Pyasina Delta found that, in poor breeding years, up to one-fifth the birds had moulted at the site previously, but that the majority of ringed birds known to be still alive were not site-faithful to their moulting grounds.